Podkolenska kotanja - Mlakar, Boštjan (Medicinski razgledi, 2000)
Topography, contents and some clinical problems of the popliteal fossa are presented. The popliteal fossa is a rhomboid-shaped intermuscular space situated at the back of the knee. It contains the popliteal artery and vein (arteria et vena poplitea), the small saphenous vein (vena saphena parva), thecommon fibular and tibial nerves (nervus fibularis communis, nervus aibialis), the popliteal lymph nodes (nodi lymphatici poplitei) and connectivetissue.
Keywords: anatomija; Knee; Anatomy and histology; histologija; kolenski sklep; Popliteal artery; Popliteal vein; Saphenous vein; Peroneal nerve